Криза кримінального права: суперечності догматів чи догматика суперечностей? - Туляков, Вячеслав Олексійович; Туляков, Вячеслав Алексеевич; Tuljakov, Vjacheslav (My University, 2009)
S o m e m o d e r n a p p r o a c h e s c o n n e c t e d with privatization of criminal legal relations, minimization of coercive powers, differentiation of criminal liability on international and m u l t i n a t i o n a l level are analyzed in this issue. The a u t h o r s t r e s s e s t h a t o r i e n t a t i o n on ancient dogmas and ideas of XIX c e n t u r y s t a n d s in contradiction with global c h a n g e s of crime and criminality. S o m e legal aspects of this problem are analyzed.
Туляков В. О. Криза кримінального права: суперечності догматів чи догматика суперечностей? / В. О. Туляков // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 296-302.
Keywords: теорія кримінального права; публічне право; приватне право; теория уголовного права; публичное право; частное право; subjective approach to proof; criminalization; fault; Public and private law